Correlation between estrogen receptor β expression and the curative effect of endocrine therapy in breast cancer patients - GUO, LIYING (D.A. Spandidos, 2014)
The aim of the present study was to investigate the association between the expression levels of estrogen receptor (ER)β and the curative effect of endocrine therapy in breast cancer patients. Cancer tissues were collected from 583 breast cancer patients between January 2000 and December 2010 and used for analysis. ERβ expression levels were determined using immunohistochemical staining. The Kaplan-Meier method was used for survival analysis and the log-rank test was conducted for difference analysis between survival times. In addition, Cox multivariate analysis was performed to analyze prognostic factors for breast cancer. In the immunohistochemical staining assay, a positive ERβ expression rate of <10% was defined as ERβ low expression, while >10% was defined as ERβ high expression. In patients expressing low levels of ERβ, the median tumor-free survival time of the patients who received endocrine therapy was significantly higher compared with that of the patients who did not receive endocrine therapy. By contrast, in patients with high ERβ expression levels, there was no significant difference in the median tumor-free survival time between the patients who received endocrine therapy and those who did not. In addition, compared with ERβ low expression patients, ERβ high expression patients had a significantly lower median tumor-free survival time. Furthermore, ERβ expression, human epidermal growth factor receptor 2 expression, tumor size, lymph node metastasis, postoperative chemotherapy, radiotherapy and endocrine therapy were identified to be independent prognostic factors for breast cancer. Therefore, high ERβ expression in breast cancer indicates poor prognosis for endocrine therapy.